Sulphonamides incorporating 1,3,5-triazine structural motifs show antioxidant, acetylcholinesterase, butyrylcholinesterase, and tyrosinase inhibitory profile - Nabih Lolak; Mehmet Boga; Muhammed Tuneg; Gulcin Karakoc; Suleyman Akocak; Claudiu T. Supuran (Taylor & Francis Group, 2020)
A series of 16 novel benzenesulfonamides incorporating 1,3,5-triazine moieties substituted with aromatic amines, dimethylamine, morpholine and piperidine were investigated. These compounds were assayed for antioxidant properties by using 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging assay, 2,2`-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid (ABTS) radical decolarisation assay and metal chelating methods. They were also investigated as inhibitors of acetylcholinesterase (AChE), butyrylcholinesterase (BChE) and tyrosinase, which are associated with several diseases such as Alzheimer, Parkinson and pigmentation disorders. These benzenesulfonamides showed moderate DPPH radical scavenging and metal chelating activity, and low ABTS cation radical scavenging activity. Compounds 2 b, 3d and 3 h showed inhibitory potency against AChE with % inhibition values of >90. BChE was also effectively inhibited by most of the synthesised compounds with >90% inhibition potency. Tyrosinase was less inhibited by these compounds.